Job satisfaction and employment characteristics of independent accountants in Greece - Σπάθης, Χαράλαμπος Τ. (SPOUDAI Journal of Economics and Business, 1999)
The current study examine the job satisfaction and employment characteristics of independent accountants in Greece. Uses a sample of 306 independent accountants from Greece. The majority of independent accountants (73%) answered that they were satisfied with their choice of career. With respect to satisfaction with i) recognition of the work of an accountant and ii) fees, this is at a satisfactory level, above the middle point of the scale. This shows, however, that independent accountants encounter a number of problems in their relations with the companies to which they provide their services. These problems have to do with the conditions holding for the practice of the accounting profession and with the recognition of their work and depend upon the institutional framework surrounding the official recognition of the profession.